Effects of preoperative and postoperative albumin levels on postoperative arrhythmias after open heart surgeries with cardiopulmonary bypass - Tural, Kevser; Kahraman, Ali (Journal of Surgery and Medicine, 2021)
Background/Aim: Ischemia-reperfusion injury is associated with transient contractility disorders and lethal arrhythmias. The main reason for this is the increase in the oxidants and the decrease in the antioxidants. This study aimed to investigate the relationship between albumin, known to have antioxidant properties, and arrhythmias seen in the early postoperative period in patients undergoing open heart surgery. Methods: Adult patients undergoing open heart surgery with cardiopulmonary bypass within 5 years were included in this single-center, retrospective cohort study. The relationship of arrhythmias within the first 24 hours after the operation with the albumin levels obtained within 6 hours before the operation and within 4 hours after the operation was investigated. The difference between preoperative and postoperative albumin levels was evaluated using the Wilcoxon test and the relationship between albumin levels and arrhythmias, using the Mann-Whitney U test. The relationship between the results was evaluated by Pearson's correlation analysis, and the interaction of the results with correlations was evaluated by regression analysis. Results: A total of 56 patients were included in the study. The average age of the patients was 63.07 years (11.24) (range, 42-89). The mean preoperative and postoperative albumin levels were 4.04 (0.51) g/dL, and 3.21 (0.45) g/dL, respectively. The mean postoperative albumin level was significantly lower than the preoperative mean albumin level (P<0.001). In the analyses performed to find the relationship between albumin levels and postoperative arrhythmias, the effects of postoperative albumin levels on postoperative arrhythmias were significant (P=0.016). In the regression analysis, there was an interaction between postoperative albumin levels and preoperative albumin levels (P<0.001), postoperative arrhythmia status (P=0.005), postoperative sinus tachycardia status (P=0.002), and postoperative lactate levels (P=0.005). Conclusion: The present study suggests that high albumin levels may have a protective effect against postoperative arrhythmias. For all that, prospective studies may be planned with more patients and by examining the biochemical mechanism more comprehensively.